Anemia pada ibu hamil dengan profilaksis klorokuin dan hubungannya dengan kejadian malaria - Agustina Tanusaputra, Soesanto Tjokrosonto dan Haripurnomo Kushadiwijaya (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Anemia is a risk factor for maternal mortality as many studies have shown. Anemia in pregnancy in Indonesia is high, between 40%-80% with Hb mean concentration of 9,7g%. Anemia caused by iron deficiency is common especially in the developing countries. The relationship between anemia and the susceptibility to malaria infection remains controversial. Researcher, noted that effectiveness of oral iron supplementation had repaired anemia. On the other hand, the others found, that iron supplementation was associated with acute exacerbations of infections, particularly malaria. Objective: The Timor Tengah Utara District in East Nusa Tenggara is a highly endemic malaria area. Maternal death as a result of malaria occurs annually. The prevalence of pregnant mothers with anemia may be similar to the other regions where oral iron supplementation is normally given to pregnant mothers. This study was therefore aimed at studying anemia in pregnant mothers who received prophylaxis and the relationship with malaria infection. Methods: This was a cohort study held from September 2000 until June 2001 in two areas of community health centers, namely Sasi and Noemuti. The subjects were 212 pregnant mothers but 33 of them were lost to follow up. Blood specimens of pregnant mothers were obtained every other week (78) and every month (101). Hemoglobin value was analyzed at the beginning and end of pregnancy. The analysis was done using survival analysis by Kaplan Meier and logistic regression. Results: The survival analysis showed differences when using cut off points under different Hb values were used. Cut off point under Hb value